2019
DOI: 10.1111/jcmm.14580
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavin‐3,3´‐digallate increases the antibacterial activity of β‐lactam antibiotics by inhibiting metallo‐β‐lactamase activity

Abstract: Metallo‐β‐lactamases (MBLs) are some of the best known β‐lactamases produced by common Gram‐positive and Gram‐negative pathogens and are crucial factors in the rise of bacterial resistance against β‐lactam antibiotics. Although many types of β‐lactamase inhibitors have been successfully developed and used in clinical settings, no MBL inhibitors have been identified to date. Nitrocefin, checkerboard and time‐kill assays were used to examine the enzyme behaviour in vitro. Molecular docking calculation, molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Traditional Chinese medicines have found uses as antibiotic replacement therapies. 54,[64][65][66] For instance, the isoquinoline alkaloid palmatine has been widely used for clinical treatments. 50,51 In this study, we found that palmatine enhanced the ciprofloxacin susceptibility of E. coli strains containing qnrS or aac(6ʹ)-Ib-cr and the effect was synergistic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional Chinese medicines have found uses as antibiotic replacement therapies. 54,[64][65][66] For instance, the isoquinoline alkaloid palmatine has been widely used for clinical treatments. 50,51 In this study, we found that palmatine enhanced the ciprofloxacin susceptibility of E. coli strains containing qnrS or aac(6ʹ)-Ib-cr and the effect was synergistic.…”
Section: Discussionmentioning
confidence: 99%
“…The fractional inhibitory concentration index (FICI) values were calculated to evaluate the combination effect as described previously. 54 Synergistic effects were interpreted according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST) as follows: FICI ≤ 0.5 represents synergy; 0.5 < FICI ≤ 4 represents no interaction; and FICI > 4 represents antagonism.…”
Section: Determination Of Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, 5 × 10 5 CFUs/mL of mid-logarithmic-phase bacterial cells in TSB (trypticase soy broth) broth were supplemented with different concentrations of IAL and then shaken under aerobic conditions at 37 • C for 4 h, and the culture supernatant was collected by centrifugation. E. coli BL21 cells carrying a β-lactamase-1 or β-lactamase-7 expression vector [24] were cultured with isopropyl-β-D-thiogalactoside to induce the expression of β-lactamases and then ultrasonicated. Then, the supernatant was collected by centrifugation and 100 µL of this supernatant was mixed with 75 µL of phosphate-buffered saline (PBS) in a 96-well microtiter plate, followed by the addition of 25 µL of nitrocefin and incubation at 37 • C for 30 min.…”
Section: Enzyme Inhibition Assaysmentioning
confidence: 99%
“…The β-lactamases of NDM-1, NDM-5 and VIM-1 were expressed and purified as described previously [20]. Briefly, the DNA sequences of NDM-1 and NDM-5 were obtained from genomic DNA of the NDM-1-positive isolates E. coli ZC-YN3 and E. coli ZC-YN5, respectively.…”
Section: Plasmid Construction and Protein Purificationmentioning
confidence: 99%